2018
DOI: 10.4103/pm.pm_170_17
|View full text |Cite
|
Sign up to set email alerts
|

In vitro induction and generation of tetraploid plants of Sophora tonkinensis Gapnep

Abstract: Background:Sophora tonkinensis Gapnep. is an important medical plant in China. Early researches of S. tonkinensis were focused on rapid propagation and quality analysis of in vitro tissue culture plantlet, and still no research focuses on the plant breeding of and there were no excellent varieties for artificial cultivation of S. tonkinensis.Objective:To set up a method to generate and select the best varieties of S. tonkinensis by polyploid breeding after induction by colchicine treatment.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These changes may provide polyploids with short-term adaptive potential (Van de Peer et al, 2017) and the opportunity to exploit new niches (e.g., Marchant et al, 2016). In addition, synthetic polyploids have been largely employed to increase agronomic traits mainly due to its higher physiological and morphological fitness compared to their natural diploids (Chung et al, 2017;Cui et al, 2017;Salma et al, 2017;Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These changes may provide polyploids with short-term adaptive potential (Van de Peer et al, 2017) and the opportunity to exploit new niches (e.g., Marchant et al, 2016). In addition, synthetic polyploids have been largely employed to increase agronomic traits mainly due to its higher physiological and morphological fitness compared to their natural diploids (Chung et al, 2017;Cui et al, 2017;Salma et al, 2017;Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…And, most of the tetraploid Sophora tonkinensis Gapnep. lines exhibited higher productivity of total contents of matrine and oxymatrine than diploids [ 35 ]. In addition, tetraploid E. purpurea had higher caffeic acid derivative and alkamide contents [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The morphological evaluation of plants is a suitable approach for the initial selection of polyploids. Plant s descriptive features constantly change with increasing chromosome numbers recognized as a gigas effect (Wei et al 2018). If these changes happen in the commercial part of the plant as in medicinal and vegetable plants, it might become a valuable feature for plant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that the most successful way to induce polyploidy is through seed treatment; as seed treatment with colchicine before germination produces more tetraploid plants rather than germinated ones (Lehrer et al 2008). Successful induction of polyploidy using colchicine was reported in some plants such as sage (S. polyploids L.) (Kobayashi et al 2008), parsley (Petroselinum crispum L.) (Nasirvand et al 2018), Sophora tonkinensis L. (Wei et al 2018) and cabbage (Brassica oleracea L.) (Albertin et al 2005).…”
mentioning
confidence: 99%